Palladium-reduced graphene oxide/metal organic framework as an efficient electrode material for battery-type supercapacitor applications - Teffu, Daniel Malesela (My University, 2021)
Recently, the use of electrochemical supercapacitors as energy storage devices has drawn great attention due to their high charge/discharge rate, long life span, high power and energy densities. However, the choice of electrode materials used is vital for the performance of supercapacitors. This study focused on the development of a low cost hybrid electrode based on reduced graphene oxide/metal organic framework composite (rGO/MOF) and a novel palladium (Pd) nanoparticles loaded on rGO/MOF termed Pd-rGO/MOF nanocomposite. The prepared nanocomposites were used for high performance electrochemical double layer capacitor-(EDLC) and battery-type supercapacitors known as supercabattery. The rGO material reported in this work was chemically derived through the oxidation reduction method using a hydrazine as a reducing agent. Furthermore, palladium nanoparticles were loaded on the rGO using the electroless plating method. The rGO/MOF and novel Pd-rGO/MOF nanocomposites were prepared using an impregnation method in dimethylformamide. The physical and morphological properties of the synthesised materials were investigated using scanning electron microscopy (SEM), transmission electron microscopy (TEM), X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), energy dispersive X-ray spectroscopy (EDX), differential scanning calorimetry (DSC) and thermogravimetric analysis (TGA). The XRD and FTIR analyses showed crystalline phases and vibrational bands for both parent materials, respectively. The TGA/DSC results showed enhancement of the thermal stability of the composite as compared to MOF material. The SEM/EDS and TEM/EDX confirmed the presence of octahedral structure of MOF in the rGO sheet like structure and elemental composition of the synthesised composite. The resultant of Pd-rGO/MOF nanocomposite showed a morphology in which a thin layer of rGO coating existed over MOF with unique bright spots indicating the presence of Pd nanoparticles. This observation agreed well with the structural properties revealed by both XRD and FTIR with the reduction of MOF intensities upon Pd-rGO loading as well as enhancement of thermal stability of the nanocomposites. The electrochemical properties of the prepared electrodes were determined using cyclic voltammetry (CV), galvanostatic charge-discharge (GCD) and electrochemical impedance spectroscopy (EIS). To evaluate the electrochemical performance of the prepared electrode materials, both two and three electrode cells were assembled. From the CV and GCD results, the nanocomposites demonstrated a battery-type behaviour and therefore asymmetric supercabattery cells were assembled using the composites as positive electrodes, and activated carbon as a negative electrode. The specific capacity of rGO/MOF in three electrode cell was found to be 459.0 C/g at a current density of 1.5 A/g in 3M potassium hydroxide. Furthermore, the asymmetric supercapacitor based on the rGO/MOF nanocomposite and activated carbon (AC) as a negative electrode exhibited a maximum energy density of 11.0 Wh/kg and the maximum power density of 640.45 W/kg. The loading of palladium nanoparticles on the nanocomposite was to improve the electrochemical active sites and the performance of the supercapacitor electrode. After incorporation of Pd nanoparticles, the specific capacitance in three electrode cell improved to 712 C/g at a higher current density of 2 A/g with the same electrolyte. The assembled supercabattery has shown improved maximum energy and energy density of 26.44 Wh/kg and 1599.99 W/kg, respectively. Based on these findings, the synthesised rGO/MOF and Pd-rGO/MOF nanocomposites are promising electrode materials for future supercabattery applications.
Thesis (M.Sc. (Chemistry)) -- University of Limpopo, 2021
Keywords: Energy; Electrode materials; Palladium; Supercapacitors; Electrochemistry -- South Africa -- Limpopo; Palladium